Cross-Sectional Area Reference Values for Sonography of Peripheral Nerves in Taiwanese Adults - Hsieh, Pei-Chen; Chang, Kuo-Hsuan; Wu, Yih-Ru; Ro, Long-Sun; Chu, Chun-Che; Lyu, Rong-Kuo; Liao, Ming-Feng; Kuo, Hung-Chou (Frontiers in Neurology, 2021)
Background: Neuromuscular ultrasound is a complementary technology that aids in the diagnosis of peripheral neuropathy. The interpretation of neuromuscular ultrasound results requires the use of accurate normative cross-sectional area (CSA) reference values. This study aims to provide CSA reference values specific to Taiwanese adults for sonography of peripheral nerves in the upper and lower extremities. Methods: The study cohort included 66 healthy subjects (36 women; 30 men). A linear probe was used to measure the CSA of the median, ulnar, radial, tibial, sural, and peroneal nerves at multiple sites. These data were analyzed to determine standard ranges for the CSA at each site (reference range = mean ± 2 × SD) and identify correlations between the CSA and patient characteristics. Results: Normative CSA ranges were determined for all the assessed nerve sites, revealing that the nerve sizes in this Taiwanese population were smaller than Caucasian populations but comparable to those reported for other Asian cohorts. Men tended to have larger nerves than women, even after adjusting for height and weight. The size of ulnar nerve in the cubital tunnel and the peroneal nerve in the popliteal fossa correlated negatively with increasing age. The nerve size correlated positively with increasing weight and BMI at several sites, correlation of median nerve in the forearm with weight and BMI was significant after multiple testing. Significant correlation was also found between size of ulnar nerve in cubital tunnel and decreasing height. Conclusion: We provide reference ranges for neuromuscular ultrasound CSA values for the upper and lower extremities that are specific to the Taiwanese population. These reference values may be useful for evaluating peripheral neuropathy in Taiwanese subjects.